Episodes. The fourth season [videorecording (DVD)] - LeBlanc, Matt; Mangan, Stephen; Greig, Tamsin, 1967-; Pankow, John; Perkins, Kathleen Rose, 1974- (Showtime Networks Inc., 2016)
Just when everybody thinks the ailing show Pucks! has been put out of its misery, the network un-cancels it. For Matt, the hits keep coming as an embezzlement scam drains his finances, forcing him to scramble for cash. Meanwhile, Pucks! creators Sean and Beverly are back on top with a hot new script, but Hollywood politics tear them right back down.